The Relationship Between Interpersonal Communication In The Family And Social Attitudes Of Adolescents In Rawang Village, Pariaman City - Tomila, Putri; Natsir, MHD (Universitas Negeri Padang, 2024)
The low social attitudes of teenagers in Rawang village are the background for this research. The lack of effective interpersonal communication in the family makes this happen. The objectives of this study are: 1) describe interpersonal communication in the family in rawang village, Pariaman City; 2) describe social attitudes in rawang village, Pariaman City; 3) see the relationship between interpersonal communication in the family with the social attitudes of adolescents in rawang village. The research approach with quantitative with correlational research type. The study population was adolescents in the village of rawang, Pariaman city which amounted to 30 people by making the research sample using stratified proportional random sampling technique. Data collection techniques using a list of questions (questionnaire) data analysis techniques using the percentage formula and product moment. The results of the study include: 1) interpersonal communication in the family in adolescents is categorized as less effective: 2) the social attitudes of adolescents in Rawang village are categorized as low; 3) there is a significant relationship between interpersonal communication in the family with the social attitudes of adolescents in Rawang village, Pariaman City. The research suggestions are 1) for parents to be able to foster the quality of interpersonal communication in the family. communication provided by parents in a family that produces a harmonious relationship; 2) for family empowerment institutions to improve the ability of parents to carry out interpersonal communication.3) Future researchers are expected to observe other variables that are related to social attitudes.Keywords: Interpersonal Communication, Adolescent Social Attitude